Hoping or discounting the future: A new perspective on the transmission of HIV/AIDS - Tony Barnett (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
Public policy debates, about HIV and prevention policy, have tended to occupy one of two extreme positions derived from either rational choice and or structuralists theories. This paper argues that the concept of hope may offer a way through this policy and paradigmatic log-jam. Hope is an individually measurable concept, which serves to link the ecological concept of risk environment with that of individual choices. It may be extended into broader understandings of the social epidemiology of some other infectious diseases. Use of an operationalized concept of hope also offers a possible way forward for rapid community diagnosis and participation in policy development, because it is immediately and intuitively accessible at three often separated levels: the individual actor, the researcher and those acting in the policy arena. The power of hope as an addition to our analytical armoury suggests that where there is hope, which requires structures and other resources if it is to be effective, then individual behaviour change in response to rational argument is possible. Where hope and resources are absent, behaviour change messages are less likely to be effective and other structural interventions, such as micro-finance, are found not only to provide income but also to offer hope. Incorporation of this variable is likely to strengthen efforts to achieve behavioural change.
Keywords: I18; H51; O19; 330; hope; health; poverty